Selection of Employees with Disabilities – Has the Burden on the Employer Become too Heavy? - Edna Rabenu; Aharon Tziner (Amfiteatru Economic Journal, 2016)
Civil rights legislation regarding people with disabilities prohibits discrimination, and guarantees that people with disabilities – including learning disorders or Attention Deficit Hyperactivity Disorders (ADHD) – have the same opportunities as everyone else. The employer is required to perform accommodations for them at the workplace such as adjusting job application procedures. It is our view that the legislation is important and necessary because it helps people with disabilities to become integrated and to contribute at work and in society. Nevertheless, to a degree, it `mistreats' the employer by not requiring applicants to disclose the accommodations that helped them with their scholastic or selection tests achievements. Thus, the employer is denied the ability to make well-informed, realistic selection decisions, and at the same time – it creates a high potential for job failure. This paper includes suggestions how to create a fair and transparent selection culture that benefits all parties – disabled applicants as well as employers.
Keywords: J5; M1; M5; 330; selection; equal opportunities; disabilities; learning disorders; ADHD